(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
A 3-spectral method for non-contact temperature measurement has been developed. Three silicon photodiodes were used. The separation of the spectrum is done by optical bandpass filters and beamspliters. It is possible to work in three modes: three-spectral, two-spectral (spectral ratio) and one-spectral. In the first mode, the temperature of objects with an unknown and variable emissivity can be measured. The last two modes give good results respectively for gray bodies and for objects with known emissivity.